Smartbin Application: A Case Study of Bin It Services Limited - Vanessa Kiwanuka Namutebi (Uganda Christian University, 2023)
This report focuses on the development of a garbage collection application to optimize waste management operations for BIN IT Services Limited Uganda. The application aims to enhance waste collection efficiency and customer experience by providing a user-friendly platform for customers to schedule and request trash pickup services. The report begins with an introduction to the importance of waste management and the challenges faced in the current system. It then outlines the objectives of the study, which include streamlining communication and scheduling, promoting environmental sustainability, and improving customer satisfaction. The literature review explores existing research and developments in the field of garbage management systems and applications, covering topics such as smart waste management, waste sorting and recycling applications, and citizen engagement through mobile applications. Additionally, the review highlights current trends in smart waste management and the transition to a circular economy. The report concludes with an analysis of Yo-Waste, a waste management company in Uganda that utilizes technology to provide waste collection, disposal, and recycling solutions. Overall, this report provides valuable insights and recommendations for the development of the garbage collection application for BIN IT Services Limited Uganda.
This is a dissertation.